Imaging Recommendations for Diagnosis, Staging, and Management of Renal Tumors - Das, Chandan J; Aggarwal, Ankita; Singh, Prabhjot; Nayak, B; Yadav, Taruna; Lal, Anupam; Gorsi, Ujjwal; Batra, Atul; Shamim, Shamim Ahmed; Duara, Bijit Kumar; Arulraj, Kevin; Kaushal, Seema; Seth, Amlesh (Indian Journal of Medical and Paediatric Oncology, 2023)
Renal cell carcinomas accounts for 2% of all the cancers globally. Most of the renal tumors are detected incidentally. Ultrasound remains the main screening modality to evaluate the renal masses. A multi -phase contrast enhanced computer tomography is must for characterizing the renal lesions. Imaging plays an important role in staging, treatment planning and follow up of renal cancers. In this review , we discuss the imaging guidelines for the management of renal tumors.
Keywords: CT scan; MRI; PET-CT scan; renal cell carcinoma; ultrasound